Peace education - Čorkalo, Dinka (2002)
The development of peace education and its basic principles are given. Discrepancies between individual and group approach has been discussed. We explored the nature of conflict, stressing its negative but also its feasible positive outcomes, since it encompasses an inner possibility for change. The article highlights the principles and theoretical foundations of peace education program, with emphasizing its role in school context. The need to internationalize national school curriculum has been stressed.
Projekt MZOS
ENG